Hydrogen Fuel Cell: Experimental Study of the Generated Voltage - Filian Arbiyani; Albertus Sentosa; Eugenia Limmuel (JST (Jurnal Sains dan Teknologi), 2025)
In recent years, global energy supply has remained heavily dependent on fossil fuels, highlighting the urgent need for renewable and clean energy sources. One promising alternative is hydrogen fuel cell technology. This study aims to examine the effect of variations in the electrode cross-sectional area immersed in the electrolyte on the electrical voltage generated by a hydrogen fuel cell system. The research employed an experimental method using two types of electrodes: ASTM C561 as the anode and AISI 304 stainless steel as the cathode. Three experimental variables were investigated, namely the percentage of electrode cross-sectional area immersed in the electrolyte, the concentration level of NaHCO₃, and the duration of electrical input applied to generate hydrogen and oxygen. The results indicate that at 100% immersion of the electrode cross-sectional area with a 50% NaHCO₃ concentration, the generated voltages were 1.91 V at 30 seconds, 1.93 V at 60 seconds, and 2.12 V at 90 seconds. The findings demonstrate that the hydrogen fuel cell is capable of producing stable and relatively constant electrical voltage, consistent with the principles of electrochemical reactions between hydrogen and oxygen. The experimental results further reveal that the magnitude of the generated voltage is influenced by factors such as hydrogen concentration, electrode surface area, as well as system temperature and humidity. The implications of this study provide a strong scientific basis for the potential utilization of hydrogen fuel cells as a clean and sustainable energy source. These findings may serve as a reference for the development of environmentally friendly alternative energy technologies, particularly in efforts to reduce dependence on fossil fuels and mitigate carbon emissions.